Inducing disorder in order: hierarchically porous covalent organic framework nanostructures for rapid removal of persistent organic pollutants - Karak, Suvendu; Dey, Kaushik; Torris, Arun; Halder, Arjun; Bera, Saibal; Kanheerampockil, Fayis; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
The key factor responsible for fast diffusion and mass transfer through a porous material is the availability of a widely open pore interior having complete accessibility from their surface. However, because of their highly stacked nature, ordered two-dimensional (2D) materials fail to find real-world applicability, as it is difficult to take advantage of their complete structure, especially the inner cores. In this regard, three-dimensional (3D) nanostructures constructed from layered two-dimensional crystallites could prove to be advantageous. However, the real challenge is to cultivate a porous nanostructure with ordered pores where the pores are surrounded by crystalline walls. Herein, a simple yet versatile in situ gas-phase foaming technique has been employed to address these cardinal issues. The use of baking soda leads to the continuous effervescence of CO2 during the crystallization of foam, which creates ripples and fluctuations on the surface of the 2D crystallites. The induction of ordered micropores within the disordered 3D architecture synergistically renders fast diffusion of various guests through the interconnected pore network. The high-density defects in the hierarchically porous structure help in ultrafast adsorption (<10 s) of various pollutants (removal efficiency of 99%) from water, all of which would lead to significant environmental benefit. The pseudo-second-order rate constant for the BPA pollutant is 182.3 g mg(-1) min(-1), which is the highest among all the literature reports to date. The high removal efficiency (highest efficiency of 94% and average efficiency of 70%) of a persistent organic pollutant has been attended for the first time.